Briant Colour Printing Joint Chapels Work-in, 1973 (London, 1973)
1973 1970-74 "Briant Colour Printing Joint Chapels Work-in, 1973" [BW0076], 1973, Trades Union Congress In June 1972, faced with one minute's notice of liquidation and closure, 130 workers at Briant Colour Printing on Old Kent Road in South London started a work-in. The trade unions to which the BCP workers belonged, mainly Society of Graphical and Allied Trades (SOGAT), the National Society of Operative Printers and Assistants (NATSOPA) and the National Graphical Association (NGA), declared the action official and consequently paid out strike support. Under the leadership of shop steward, Bill Freeman, the workers occupied the plant and stayed for over a year until July 1973 when a new owner was found. However the works finally closed in November 1973. Whilst under workers' control, the worker occupation became the unofficial print shop for the struggles of the day.